Older People's External Residential Assessment Tool (OPERAT): a complementary participatory and metric approach to the development of an observational environmental measure - Vanessa Burholt; Matthew Steven Roberts; Charles Brian Alexander Musselwhite (BMC, 2016)
Abstract Background The potential for environmental interventions to improve health and wellbeing has assumed particular importance in the face of unprecedented population ageing. However, presently observational environmental assessment tools are unsuitable for 'all ages'. This article describes the development of the Older People's External Residential Assessment Tool (OPERAT). Methods Potential items were identified through review and consultation with an Expert Advisory Group. Items were ranked according the importance ascribed to them by older people who responded to a survey distributed by 50+ forum in Wales (N = 545). 40 highly ranked items were selected for the OPERAT pilot. An observational assessment was conducted in 405 postcodes in Wales. Items validated with data from a survey of older residents (N = 500) in the postcode areas were selected for statistical modelling (Kendall's Tau-b, p < .05). Data reduction techniques (exploratory factor analysis with Geomin rotation) identified the underlying factor structure of OPERAT. Items were weighted (Thurstone scaling approach) and scores calculated for each domain. Internal consistency: all items were tested for scale-domain total correlation (Spearman's rank). Construct validity: correlation analysis examined the associations between domains and the extent to which participants enjoyed living in the area, felt that it was a desirable place to live, or felt safe at night or during the day (Spearman's rank). Usability: analysis of variance compared mean OPERAT domain scores between neighbourhoods that were homogenous in terms of (a) deprivation (quintiles of the Townsend Index) and (b) geographic settlement type. Inter-rater reliability: Krippendorff's alpha was used to evaluate inter-rater consistency in ten postcode areas. Results A four factor model was selected as the best interpretable fit to the data. The domains were named Natural Elements, Incivilities and Nuisance; Navigation and Mobility; and Territorial Functioning. Statistical tests demonstrated good internal consistency, convergent validity, utility and inter-rater reliability. Conclusions Participatory approaches to research and robust statistical testing are not mutually exclusive. OPERAT can be used to assess the suitability of external residential environments for older people with different physical and cognitive capacities, living in rural or urban areas. OPERAT can be used to help plan residential environments that are friendly for all ages.